Paris-Amsterdam Underground : Essays on Cultural Resistance, Subversion, and Diversion - Hussey, Andrew; Lindner, Christoph, 1971- (Cities and cultures., 2020)
The postwar histories of Paris and Amsterdam have been significantly defined by the notion of the "underground" as both a material and metaphorical space. Examining the underground traffic between the two cities, this book interrogates the countercultural histories of Paris and Amsterdam in the mid to late-twentieth century. Shuttling between Paris and Amsterdam, as well as between postwar avant-gardism and twenty-first century global urbanism, this interdisciplinary book seeks to create a mirroring effect over the notion of the underground as a driving force in the making of the contemporary European city.